Kansas Beef Industry Economic Trends - Dhuyvetter, Kevin C.; Graff, Jennifer; Kuhl, Gerry L. (My University, 1998)
This publication describes the multibillion-dollar Kansas beef industry.
MF1057_1998_02
Keywords: MF1057; Livestock; Economics; MF